Difference between bone age at the hand and elbow at the onset of puberty. Issue 1 (7th January 2022) - Jang, Woo Young; Ahn, Kyung-Sik; Oh, Saelin; Lee, Ji Eun; Choi, Jimi; Kang, Chang Ho; Kang, Woo Young; Hong, Suk-Joo; Shim, Eddeum; Kim, Baek Hyun; Je, Bo-Kyung; Jung, Hae Woon; et al.
Abstract : Abstract: In the pubertal period, bone age advances rapidly in conjunction with growth spurts. Precise bone-age assessments in this period are important, but results from the hand and elbow can be different. We aimed to compare the bone age between the hand and elbow around puberty onset and to elucidate the chronological age confirming puberty onset according to elbow-based bone age. A total of 211 peripubertal subjects (127 boys and 84 girls) who underwent hand and elbow radiographs within 2 months was enrolled. Two radiologists and a pediatric orthopedic surgeon assessed bone age. Hand bone age was graded using the Greulich–Pyle (GP) method, and elbow bone age was determined using the Sauvegrain method. The correlation of 2 methods was evaluated by Demining regression analysis, and the mean absolute difference (MAD) with chronological age was compared between pre-pubertal and pubertal subjects. Receiver-operating characteristic curve analysis was performed to determine the chronological age confirming puberty onset. There was a statistically significant difference in bone age revealed by the GP and Sauvegrain methods in the pubertal group. In the pubertal group, the MAD was 1.26 ± 0.90 years with the GP method and 0.61 ± 0.47 years with the Sauvegrain method in boys ( P < .001), while in girls, the MAD was 0.84 ± 0.60 years and 0.53 ± 0.36 years with the same 2 methods ( P = .033). The chronological age for confirming puberty onset using the elbow was 12.2 years in boys and 10.3 years in girls. The bone ages of hand and elbow were different at puberty, and the elbow was a more reliable location for bone-age assessment at puberty. Puberty onset according to elbow occurred slightly earlier than expected.